Molecular and biochemical basis for the loss of bioluminescence in the dinoflagellate Noctiluca scintillans along the west coast of the U.S.A. (19th August 2019) - Valiadi, Martha; de Rond, Tristan; Amorim, Ana; Gittins, John R.; Gubili, Chrysoula; Moore, Bradley S.; Iglesias‐Rodriguez, Maria Debora; Latz, Michael I.
Abstract: The globally distributed heterotrophic dinoflagellate Noctiluca scintillans (Macartney) Kofoid & Swezy is well known for its dense blooms and prominent displays of bioluminescence. Intriguingly, along the west coast of the U.S.A., its blooms are not bioluminescent. We investigated the basis for this regional loss of bioluminescence using molecular, cellular, and biochemical analyses of isolates from different geographic regions. Several prominent differences were identified in the nonbioluminescent strains: (1) the fused luciferase and luciferin binding protein gene ( lcf/lbp ) was present but its transcripts were undetectable; (2) lcf/lbp contained multiple potentially deleterious mutations; (3) the substrate luciferin was absent, based on the lack of luciferin blue autofluorescence and the absence of luciferin‐derived metabolites; (4) although the cells possessed scintillons, the organelles that contain the luminescent chemistry, electron microscopy revealed additional scintillon‐like organelles with an atypical internal structure; and (5) cells isolated from the California coast were 43% smaller than bioluminescent cells from the Gulf of Mexico. Phylogenetic analyses based on large subunit rDNA did not show divergence of the nonbioluminescent population in relation to bioluminescent N. scintillans from the Pacific Ocean and Arabian Sea. This study demonstrates that gene silencing and the lack of the luciferin substrate have resulted in the loss of an important dinoflagellate functional trait over large spatial scales in the ocean. As the bioluminescence system of dinoflagellates is well characterized, nonbioluminescent N. scintillans provide an ideal model to explore the evolutionary and ecological mechanisms that lead to intraspecific functional divergence in natural dinoflagellate populations.